Improved fluorescent labeling of chitin oligomers: Chitinolytic properties of acidic mammalian chitinase under somatic tissue pH conditions. (15th May 2017) - Wakita, Satoshi; Kimura, Masahiro; Kato, Naoki; Kashimura, Akinori; Kobayashi, Shunsuke; Kanayama, Naoto; Ohno, Misa; Honda, Shotaro; Sakaguchi, Masayoshi; Sugahara, Yasusato; Bauer, Peter O.; Oyama, Fumitaka
Highlights: Pre-acidification method for labeling chitin oligomers by a fluorophore. AMCase produced (GlcNAc)2 at strong acidic to neutral condition. AMCase produced (GlcNAc)3 at pH above 5.0. AMCase degrades chitin substrates in a pH dependent manner. Abstract: Acidic mammalian chitinase (AMCase) has been implicated in various pathophysiological conditions including asthma, allergic inflammation and food processing. AMCase is most active at pH 2.0, and its activity gradually decreases to up to pH 8. Here we analyzed chitin degradation by AMCase in weak acidic to neutral conditions by fluorophore-assisted carbohydrate electrophoresis established originally for oligosaccharides analysis. We found that specific fragments with slower-than-expected mobility as defined by chitin oligosaccharide markers were generated at pH 5.0 ∼ 8.0 as by-products of the reaction. We established an improved method for chitin oligosaccharides suppressing this side reaction by pre-acidification of the fluorophore-labeling reaction mixture. Our improved method specifically detects chitin oligosaccharides and warrants quantification of up to 50 nmol of the material. Using this strategy, we found that AMCase produced dimer of N -acetyl-d -glucosamine (GlcNAc) at strong acidic to neutral condition. Moreover, we found that AMCase generates (GlcNAc)2 as well as (GlcNAc)3 under physiological conditions.